A Five-Year Single-Surgeon Experience: Continuous Series of Microvascular Free Flap and Factors Influencing Its Viability - Atmodiwirjo, Parintosa; Mochtar, Rezania; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester; Ralena, Nadhira Anindita (Jurnal Plastik Rekonstruksi, 2025)
Background: Over the past years, microvascular free tissue transfer has become increasingly popular in the field of plastic surgery. Our center has also been actively performing these complex surgeries for extensive defect closure. In this study spanning five years, our objective is to examine the challenges commonly encountered in free flap reconstruction and identify factors that contribute to the failure of such flaps, with the ultimate goal of enhancing our learning curve.Methods: This article presents a retrospective analysis of all patients who underwent microvascular free tissue transfer procedures performed by a single surgeon (PA) and teams of Plastic Reconstructive and Aesthetic Surgery residents from 2014 to 2018. Multivariate analysis was conducted to identify the factors associated with free flap failure.Results: Between 2014 and 2018, a total of 203 microvascular free tissue transfers were performed to reconstruct defects at various anatomical sites. The overall viable flap rate for microvascular free flap reconstructions, irrespective of the indication or anatomical location, was found to be 90.6%. The type of flap, whether it was a perforator or non-perforator flap, emerged as the main significant factor influencing free flap viability.Conclusion: Microvascular free tissue transfer represents an excellent reconstructive option for addressing large defects requiring extensive or composite flaps. By acknowledging the factors contributing to free flap failure, we can optimize outcomes and provide the best possible results for our patients.